Freedom in community or freedom in solitude? Remarks on republicanism and liberalism - Bocheński, Tobiasz Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
A political thought is an area of legitimate contribution of competitive ideas. Liberalism is often considered as one of the most significant and influential paradigm of our times. The common acceptance of liberal conception of negative liberty can be acknowledged as a proof of this tendency. At the same time clearly visible is the renaissance of republicanism and the conception of active participation in governance. The liberal and republican assumptions have similar roots but different social practices. The aim of this paper is to examine in contrast liberal and republican conceptions of freedom. The author discusses main categories of both political traditions: state, commonwealth, common good, citizen, individualism, law, limited power and freedom itself. The author attempts to compere republicanism and liberalism as the competitive political paradigms to show the dilemmas of modern states and societies where there is no common consensus referring to definition of liberty.